5 - Seeing the State through Youth Policy Formation: The Case of the State of Jharkhand - Sinha-Kerkhoff, Kathinka (Africa Development, 2021)
This article explores the way in which one of the largest semi-autono- mous states in India, the state of Jharkhand, is developing policies that target the youth. It also looks at ways in which it is providing room for youths to participate in processes of decision making. Studying the state government’s position, ideology and praxis in this regard demon- strates that there is an interesting process of transmission of socio- political power into the hands of the young in such a way that the youth is likely to become a supporter and protector of the state. On the part of the government, a great deal of trust exists with regard to youth involvement in policies beneficial to the pursuit of an ideal welfare package for the people. The state makes sure that certain social and economic benefits flow towards the youth, and this certainly helps in securing their support for its notion of a semi-autonomous state, with the belief inculcated in the youth that the future is in their hands.